Associação entre horas de sono, fatores demográficos antropométricos e dietéticos de crianças e adolescentes de uma escola do Sul do Brasil (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Association among sleep hours, demographic, anthropometric and dietary factors of children and adolescents from a school in the South of Brazil